Height Matters? Examining Position-Specific Anthropometric Differences in Football Players - Muhammad Reza Aziz Prasetya; Awang Firmansyah; Heri Wahyudi; Safeyn Sadaat Mridul (Indonesian Journal of Kinanthropology (IJOK), 2026)
Background: Height is an important anthropometric factor in football and may influence positional roles and performance. Players in different positions are required to perform specific tasks, which may lead to differences in physical characteristics such as height. However, evidence on height differences across playing positions is still limited. Methods: This study analyzed data from 100 football players (20 per position). Mean height was compared across positions using one-way ANOVA, followed by Tukey post hoc test to identify pairwise differences. Results: There was a significant difference in height across playing positions (F(4, 95) = 13.26, p < 0.001). Goalkeepers showed the greatest mean height (189.80 cm), followed by defenders (183.85 cm), attackers (182.40 cm), unspecified players (180.95 cm), and midfielders (177.95 cm). Tukey post hoc analysis showed that goalkeepers were significantly taller than all other positional groups, while defenders were significantly taller than midfielders. Conclusions: Height differs across playing positions in football and reflects position-specific demands. These findings suggest that height can be considered in talent identification and player selection, particularly for positions that require aerial ability. However, performance in football is influenced by multiple factors, not height alone.